2022
DOI: 10.1101/2022.06.07.495155
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

MARSY: A multitask deep learning framework for prediction of drug combination synergy scores

Abstract: Motivation: Combination therapies have emerged as a treatment strategy for cancers to reduce the probability of drug resistance and to improve outcome. Large databases curating the results of many drug screening studies on preclinical cancer cell lines have been developed, capturing the synergistic and antagonistic effects of combination of drugs in different cell lines. However, due to the high cost of drug screening experiments and the sheer size of possible drug combinations, these databases are quite spars… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 49 publications
(67 reference statements)
0
14
0
Order By: Relevance
“…Here we considered replacing the original embeddings in CPA with the embeddings from GPT 3.5, enlarging the accessibility for drug embeddings. for model evaluation based on datasets D1 [14] and D2 [17]. For classification, we included ROC-AUC (ROCAUC) and Accuracy (ACC) for model evaluation based on datasets D1 and D3 [18].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Here we considered replacing the original embeddings in CPA with the embeddings from GPT 3.5, enlarging the accessibility for drug embeddings. for model evaluation based on datasets D1 [14] and D2 [17]. For classification, we included ROC-AUC (ROCAUC) and Accuracy (ACC) for model evaluation based on datasets D1 and D3 [18].…”
Section: Resultsmentioning
confidence: 99%
“…• MARSY [17]: MARSY is a DNN-based method with multi-task learning framework for drug synergistic effect prediction. This method can only handle the regression task.…”
Section: Msementioning
confidence: 99%
See 1 more Smart Citation
“…MARSY [El Khili et al, 2023], which uses a drug-drug representation network combined with the latent representation learner of DeepSynergy.…”
Section: Methodsmentioning
confidence: 99%
“…However, drug induced gene expression signatures contain more context specific biological information regarding drug effect than chemical structure, thus their application for drug synergy prediction can be beneficial. Using drug signatures has been used to predict synergistic effects of anticancer drugs (Bansal et al, 2014), and a recent benchmarking study showed that machine learning models using expression based features significantly outperform standard, chemical feature based methods (El Khili et al, 2022). Interestingly, several of these studies suggest that similarity between drug signatures is a strong predictor of synergistic drug effect (Diaz et al, 2020), suggesting drugs targeting the same pathway, but at different targets are generally more synergistic.…”
Section: Identifying Synergistic Drug Combinationsmentioning
confidence: 99%